Polymerase Chain Reaction Method for Detection of Vibrio parahaemolyticus in Seafood from Wet Market in Kuching and Kota Samarahan - Tan, Shoo Kiong (Universiti Malaysia Sarawak, UNIMAS, 2010)
V. parahaemolyticus is prevalent in tropical marine environment in all seasons and can cause gastroenteritis associated with consumption of raw or undercooked seafood. This study was aimed to determine the occurrence of V. parahaemolyticus in seafood purchased from wet markets in Kuching and Kota Samarahan and to detect the presence of virulent strains carrying the thermostable direct hemolysin (tdh) and TDH-related hemolysin (trh) genes using PCR. A total of 54 seafood samples including shrimp, cockle and squid were subjected to PCR targeting the toxR gene for detection of V. parahaemolyticus. There were 35 samples positive for toxR gene by which shrimp and squid each comprised of 34.3% of the samples and 31.4% of the positive samples were cockle. In the PCR detection for virulent properties of V. parahaemolyticus, 12 samples showed positive result for tdh gene while only 1 sample showed presence of trh gene. Hence, detection of virulent strains of V. parahaemolyticus in seafood harvested from marine environment in Malaysia suggests a probable risk for health of people consuming raw or partially cooked seafood.